Colonial legacies and social welfare regimes in Africa: An empirical exercise - Thandika Mkandawire (United Nations Research Institute for Social Development (UNRISD), 2016)
This paper identifies three types of welfare regimes in Africa, based on the insight that tax and expenditure regimes are closely associated. Using cluster analysis, the author highlights historical legacies in current welfare policies, demonstrating that welfare regimes in Africa have been strongly determined by the ways in which different countries were incorporated into the colonial economy. The author finds that many of the new social welfare reforms are taking place in what he refers to as labour reserve economies, and are generally internally rather than aid-driven. He stresses the importance of thinking of social expenditure in relationship to domestic resource mobilization, and finds that the focus on aid and social expenditure has tended to obscure this important aspect of welfare regimes in Africa.
Keywords: 330